Effects of Dietary Zinc Sources on Growth Performance and Gut Health of Weaned Piglets - Diao, Hui; Yan, Jiayou; Li, Shuwei; Kuang, Shengyao; Wei, Xiaolan; Zhou, Mengjia; Zhang, Jinxiu; Huang, Chongbo; He, Peng; Tang, Wenjie (Frontiers in Microbiology, 2021)
The present study aimed to investigate the effects of dietary zinc sources on the growth performance and gut health of weaned piglets. In total, 96 Duroc × Landrace × Yorkshire (DLY) weaned piglets with an initial average body weight of 8.81±0.42kg were divided into four groups, with six replicates per treatment and four pigs per replicate. The dietary treatment groups were as follows: (1) control group, basal diet; (2) zinc sulphate (ZnSO4) group, basal diet +100mg/kg ZnSO4; (3) glycine zinc (Gly-Zn) group, basal diet +100mg/kg Gly-Zn and (4) zinc lactate group, and basal diet +100mg/kg zinc lactate. The whole trial lasted for 28days. Decreased F/G was noted in the Gly-Zn and zinc lactate groups (p<0.05). The zinc lactate group had a lower diarrhea rate than the control group (p<0.05). Moreover, the ZnSO4, Gly-Zn, and zinc lactate groups had significantly higher apparent total tract digestibility of dry matter (DM), crude protein (CP), ether extract (EE), crude ash, and zinc than the control group (p<0.05). The Gly-Zn and zinc lactate groups had higher jejunal villus height and a higher villus height:crypt depth ratio than the control group (p<0.05). In addition, the ZnSO4, Gly-Zn and zinc lactate groups had a significantly lower mRNA expression level of jejunal ZRT/IRT-like protein 4 (ZIP4) and higher mRNA expression level of jejunal interleukin-1β (IL-1β) than the control group (p<0.05). The mRNA expression level of jejunal zinc transporter 2 (ZNT2) was higher and that of jejunal Bcl-2-associated X protein (Bax) was lower in the Gly-Zn and zinc lactate groups than in the control group (p<0.05). Moreover, the zinc lactate group had a higher count of Lactobacillus spp. in the cecal digesta and higher mRNA expression levels of jejunal occludin and mucin 2 (MUC2) than the control group (p<0.05). In conclusion, dietary supplementation with 100mg/kg ZnSO4, Gly-Zn, or zinc lactate could improve the growth performance and gut barrier function of weaned piglets. Dietary supplementation with organic zinc, particularly zinc lactate, had the best effect.